Directions of Al-mansubāt in (Maʿānī Al-qurʾān Wa ʾʿrābih LiZZajjāj) A study in the optimality theory “OT” - Al-Qaisi, Ahmed (Al-Adab Journal, 2025)
Objectives: This research aims to apply the optimality theory “OT” on Al-Mansūbāt Maʿānī Al-qurʾān Waʾʿrābih LiZZajjāj and to monitor the observations and shortcomings of this modern Western theory when applied to the syntactic aspect of the Arabic language. Methods: The research followed a descriptive approach, employing the OT theory "Linguistic Superiority Table" Results: The research found out: - The failure to recognize all the characteristics and criteria of language leads to a major deviation in the differential analysis of linguistic material, because the absence of conditions and criteria that determine the grammatically acceptable sentence or the grammatically optimal sentence leaves the door wide open for interpretation (linguistic chaos). - The difficulty of agreeing on grammatical preference tables, which are referred to in syntactic issues, due to the large number of grammatical constraints that sometimes conflict and there are no clear grammatical arguments in them, and if there are, they are disputed. - It is not necessary for the optimal witness in a certain differential space to obtain the linguistic preference in another differential space. - The difficulty of deciding on usage preference, because we do not know how much we judge the witness to be frequently used or infrequently used, in other words, what is the magnitude of this abundance? Conclusion: There are many shortcomings of the theory when applied to the syntactic level of the Arabic language, and it cannot be applied in its western concept on this linguistic level, but the researcher tried to develop the theory in accordance with the specificity of Arabic.